Acute Impact of Moderate-Intensity and Vigorous-Intensity Exercise Bouts on Daily Physical Activity Energy Expenditure in Postmenopausal Women. (1st August 2010) - Wang, Xuewen; Nicklas, Barbara J.
Abstract : This study determined whether performing a single moderate- or vigorous-intensity exercise bout impacts daily physical activity energy expenditure (PAEE, by accelerometer). Overweight/obese postmenopausal women underwent a 5-month caloric restriction and moderate- (n = 18 ) or vigorous-intensity (n = 18 ) center-based aerobic exercise intervention. During the last month of intervention, in women performing moderate-intensity exercise, PAEE on days with exercise (577.7 ± 219.7 kcal·d −1 ) was higher (P = .011 ) than on days without exercise (450.7 ± 140.5 kcal·d −1 ); however, the difference (127.0 ± 188.1 kcal·d −1 ) was much lower than the energy expended during exercise. In women performing vigorous-intensity exercise, PAEE on days with exercise (450.6 ± 153.6 kcal·d −1 ) was lower (P = .047 ) than on days without exercise (519.2 ± 127.4 kcal·d −1 ). Thus, women expended more energy on physical activities outside of prescribed exercise on days they did NOT perform center-based exercise, especially if the prescribed exercise was of a higher intensity.